2020
DOI: 10.1001/jamanetworkopen.2020.6653
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a Machine Learning Model Based on Pretreatment Symptoms and Electroencephalographic Features to Predict Outcomes of Antidepressant Treatment in Adults With Depression

Abstract: IMPORTANCE Despite the high prevalence and potential outcomes of major depressive disorder, whether and how patients will respond to antidepressant medications is not easily predicted. OBJECTIVE To identify the extent to which a machine learning approach, using gradient-boosted decision trees, can predict acute improvement for individual depressive symptoms with antidepressants based on pretreatment symptom scores and electroencephalographic (EEG) measures. DESIGN, SETTING, AND PARTICIPANTS This prognostic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…For example, in a recent study in a sample of 81,630 adults, treatment-specific predictive models from electronic health record data did not perform better than general treatment response models ( 48 ). A classifier capable of predicting treatment response to a focused range of options (e.g., SSRIs) could arguably hold higher clinical utility in practice than one that predicts response to a single agent ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study in a sample of 81,630 adults, treatment-specific predictive models from electronic health record data did not perform better than general treatment response models ( 48 ). A classifier capable of predicting treatment response to a focused range of options (e.g., SSRIs) could arguably hold higher clinical utility in practice than one that predicts response to a single agent ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible associations between clinical perceptions and measurements were also investigated. An enormous amount of EEG data remains to be explored using informatics and advances in this field, such as machine learning and artificial intelligence [ 22 ]. With these, the brain activities of patients related to anxiety and alertness, as well as pain and other effects, after local anesthesia and the administration of anxiolytic drugs may be observed with more clarity.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that, by considering most of the evaluated symptoms and the relevance of pretreatment EEG data, machine learning had satisfactory discriminative performance for treatment response. 66 Drysdale et al used neuroimaging biomarkers defined by resting-state connectivity to identify biotypes capable of predicting treatment response for depression with repetitive TMS. For instance, 82.5% of the individuals categorized as biotype 1 presented a significant improvement to repetitive TMS, compared to 25% of those with biotype 2, even though these two biotypes were associated with similar fatigue and anergia symptomatology.…”
Section: Precision Psychiatry and Treatment-resistant Bipolar Depressionmentioning
confidence: 99%